2007
DOI: 10.1088/0029-5515/47/10/s13
|View full text |Cite
|
Sign up to set email alerts
|

Overview of recent physics results from the National Spherical Torus Experiment (NSTX)

Abstract: The National Spherical Torus Experiment (NSTX) has made considerable progress in advancing the scientific understanding of high performance long-pulse plasmas needed for future spherical torus (ST) devices and ITER. Plasma durations up to 1.6 s (five current redistribution times) have been achieved at plasma currents of 0.7 MA with non-inductive current fractions above 65% while simultaneously achieving β T and β N values of 17% and 5.7 (%m T MA −1 ), respectively. A newly available motional Stark effect diagn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
0
4

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
2
1

Relationship

4
5

Authors

Journals

citations
Cited by 47 publications
(40 citation statements)
references
References 44 publications
3
33
0
4
Order By: Relevance
“…In particular, precise rtEFIT/isoflux [14,15] control of the plasma boundary during the current ramp-up phase at high elongation required the real-time acquisition of additional magnetic field sensors in the divertor region and a more accurate vessel current model [16] with additional measurements. Although not the subject of this paper, the control system data acquisition was also expanded to include capabilities for resistive wall mode feedback experiments [17] and error field control experiments [18] as described in [11]. Whereas the expanded technical capabilities were in place at the end of 2005, the first NSTX run that took full advantage of these capabilities was in 2006.…”
Section: Improvements In Plasma Shaping Capability On Nstxmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, precise rtEFIT/isoflux [14,15] control of the plasma boundary during the current ramp-up phase at high elongation required the real-time acquisition of additional magnetic field sensors in the divertor region and a more accurate vessel current model [16] with additional measurements. Although not the subject of this paper, the control system data acquisition was also expanded to include capabilities for resistive wall mode feedback experiments [17] and error field control experiments [18] as described in [11]. Whereas the expanded technical capabilities were in place at the end of 2005, the first NSTX run that took full advantage of these capabilities was in 2006.…”
Section: Improvements In Plasma Shaping Capability On Nstxmentioning
confidence: 99%
“…This is an important step towards using the HHFW as a tool for driving current during the startup phase of the NSTX plasma to aid plasma current ramp-up. The HHFW experiments are described in more detail in [18].…”
Section: Rf Heating and Current Drivementioning
confidence: 99%
“…2 While the present fusion devices can tolerate the energy loss from these events, type I ELMs in future high-power machines can cause a transient heat load on the plasma facing components ͑PFCs͒ that exceeds the power handling capabilities of the materials and have a severe impact on the lifetime of the PFCs and divertor components. 3 On the National Spherical Torus Experiment ͑NSTX͒ device, 4 ELM behavior is similar to that of conventional, large aspect ratio machines, with a few exceptions. A small, type V ELM regime has been identified that combines the favorable edge density control and impurity particle handling properties of ELMs with a low transient peak heat flux.…”
Section: Introductionmentioning
confidence: 91%
“…The TRANSP analysis code [53,54] uses measured temperature and density (including impurity) profiles, rotation velocity and radiated power to compute the beam ion deposition and density using a Monte-Carlo approach to determine the sources and losses of energy AFID has been applied, for example, to MHD-induced energetic ion redistribution and/or loss effects in simulations of the E||B NPA spectra [13] including horizontal and vertical scanning measurements, in transport [55] and in beam-driven plasma current [3,56]. In the following analysis, the TRANSP option to follow the fast ion gyro-orbit is used (as opposed to the guiding center).…”
Section: Transp Code Analysismentioning
confidence: 99%